Incidence and pattern of traumatic spinal fractures and associated spinal cord injury resulting from motor vehicle collisions in China over 11 years: An observational study. Issue 43 (October 2016) - Wang, Hongwei; Liu, Xinwei; Zhao, Yiwen; Ou, Lan; Zhou, Yue; Li, Changqing; Liu, Jun; Chen, Yu; Yu, Hailong; Wang, Qi; Han, Jianda; Xiang, Liangbi
Abstract : Abstract: To investigate the incidence and pattern of traumatic spinal fractures (TSFs) and associated spinal cord injury (SCI) resulting from motor vehicle collisions (MVCs). This was a cross-sectional study. We retrospectively reviewed 698 patients with TSFs resulting from MVCs admitted to our university-affiliated hospitals from 2001 to 2011. The incidence and pattern were summarized with respect to different age groups, fracture levels, and the role of patients. There were 464 males (66.5%) and 234 females (33.5%) aged 40.5 ± 13.8 years old. The most common roles of patients in MVCs were car drivers (189, 27.1%), pedestrians hurt by a car (155, 22.2%), and car passengers (145, 20.8%). The most common fracture levels were L1 (n = 198, 19.2%) and T12 (n = 116, 11.3%), followed by C2 (n = 86, 8.3%). A total of 298 (42.7%) patients suffered a spinal cord injury. The frequencies of SCIs decreased from 53.1% to 24.6% with increasing age. The patients in the 20 to 39 age group (45.3% of all patients) had the largest sex ratio (2.4) and highest frequency of complete SCIs (19.3%) and complications (3.2%). Motorcycle drivers had the youngest mean age (35.7 ± 10.2), largest sex ratio (10.4), and highest frequency of SCIs (56.0%) and complications (4.4%). Motorcycle passengers had the highest frequency of complete SCI (22.7%) and ASOIs (45.5%) and the largest mean injury severity scoring (ISS) (18.9 ± 9.6). The most common fracture levels of motorcycle drivers were C3–C7, while that of others were T11–L2. The most common role of patients who sustained TSFs were car drivers who were 20 to 39 years old. Motorcycle drivers had the highest frequency of SCIs and complications. Motorcycle passengers had the highest frequency of complete SCIs and ASOIs and the largest ISS. Therefore, we should pay more attention to MVC patients, especially car drivers and motorcycle drivers and passengers.